The Digital Zenith Camera TZK2-D - A Modern High-Precision Geodetic Instrument for Automatic Geographic Positioning in Real-Time - Hirt, Christian (Astronom Society Pacific, 2003)
The digital zenith camera TZK2-D is a geodetic state-of-the-artinstrumentation for determining geographic longitude and latitudefully automatically. Using CCD technology for imaging stars anda GPS-receiver for precise time measurement, this instrument allows real-time geographic positioning with an accuracy of 0.2 seconds of arc. The digital zenith camera is used for fast and high-precision determination of the plumb line and its vertical deflection applied for the local gravity field determination in geodesy. In astronomy, high-precision pointing of large telescopes can be supported by the knowledge of the plumb line and is vertical deflection provided by the digital zenith camera in combination with a GPS receiver. The digital zenith camera TZK2-D is a geodetic state-of-the-art instrumentation for determining geographic longitude and latitude fully automatically. Using CCD technology for imaging stars anda GPS-receiver for precise time measurement, this instrument allows real-time geographic positioning with an accuracy of 0.2 seconds of arc. The digital zenith camera is used for fast and high-precision determination of the plumb line and its vertical deflection applied for the local gravity field determination in geodesy. In astronomy, high-precision pointing of large telescopes can be supported by the knowledge of the plumb line and its vertical deflection provided by the digital zenith camera in combination with a GPS receiver.